Sustainability of Community-Based Management of Lerak Spring in Semarang City - Purwadi, Cintiya Egi; Shabrina, Dhiyanita; Gunawan, Mahendra; Trihadianta, Mohammad Rifki; Mustikawati, Lenny Helmalia; Jabbar, Abdul; Fariz, Trida Ridho; Haris, Amnan (Journal of Environmental and Science Education, 2023)
Along with the increase in the need and use of water, a sustainable water management and distribution system must be implemented. A sound water distribution system requires a proper management and distribution system. Gunungpati District is one of the areas in Semarang City that still utilizes springs as a source of clean water to meet daily needs. One of the springs utilized to meet the clean water needs of residents is Lerak Spring, located in Muntal Village RT 1 RW 6, Pakintelan Village. This study aimed to determine the management of the spring and its sustainability aspects. Data collection methods used in this study consisted of primary data using qualitative methods in the form of interviews, observations, and laboratory tests related to water quality. The results showed that the management of Lerak Spring needs to have a relatively low level of sustainability in terms of social, economic, environmental, cultural, and technical aspects.